Development of mental health first-aid guidelines for a person after a potentially traumatic event: A Delphi expert consensus study in Argentina and Chile - Agrest, Martín (2024)
Background: Exposure to potentially traumatic events increases the risk of a person developing a mental disorder. Training community members to offer support to a person during and after a traumatic situation may help lower this risk. This study reports on the cultural adaptation of Australian mental health first aid guidelines for individuals exposed to a potentially traumatic event to the Chilean and Argentinian context.Methods: A Delphi expert consensus study was conducted with two panels of experts, one of people with lived experience of trauma (either their own or as a carer; n = 26) and another one of health professionals (n = 41). A total of 158 items, drawn from guidelines developed by Australian experts in 2019, were translated to Spanish and evaluated in a two-round survey process. The panellists were asked to rate each item on a five-point Likert scale; statements were included in the final guidelines if 80% of both panels endorsed the item as “essential” or “important”.Results: Consensus was achieved on 142 statements over two survey rounds. A total of 102 statements were included from the English-language guidelines, and 40 locally generated statements were accepted in the second round. Local experts endorsed a larger number of items compared to their counterparts in Australia and emphasised the importance of acknowledging the first aider’s limitations, both personally and as part of their helping role. Additional items about working as a team with other first responders and considering helping the person’s significant others were endorsed by the local panellists.Conclusions: The study showed a high level of acceptance of the original actions suggested for inclusion in the guidelines for Australia, but also a significant number of new statements that highlight the importance of the adaptation process. Further research on the dissemination of these guidelines into a Mental Health First Aid training course for Chile and Argentina is still required.